2000
DOI: 10.1016/s0042-6989(00)00055-9
|View full text |Cite
|
Sign up to set email alerts
|

Human development of perceptual organization

Abstract: Two relevant dimensions are revealed within which developmental patterns of perceptual organization might be investigated. Within the local-integrative dimension, employing a contour integration task, we found indications that spatial integration develops slowly. We also found reduced contextual modulation of a local target in children employing the Ebbinghaus illusion. Within the action-perception dimension, we hypothesize a relatively slow development of the perceptual system (mediated by the ventral visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
151
4
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 201 publications
(173 citation statements)
references
References 71 publications
15
151
4
3
Order By: Relevance
“…They argue that the visual system of 4-5-year-old children is not sufficiently mature to integrate entire images spatially, thus they see more piecemeal rivalry than adults. This is in line with their earlier findings in contour integration (Kovács, 2000) or spatial integration (Káldy and Kovács, 2003).…”
Section: Development Of Binocular Visionsupporting
confidence: 93%
See 2 more Smart Citations
“…They argue that the visual system of 4-5-year-old children is not sufficiently mature to integrate entire images spatially, thus they see more piecemeal rivalry than adults. This is in line with their earlier findings in contour integration (Kovács, 2000) or spatial integration (Káldy and Kovács, 2003).…”
Section: Development Of Binocular Visionsupporting
confidence: 93%
“…There is an observable inhomogeneity in the development of different visual functions and the maturation of neuroanatomical circuits participating in visual information processing. In contrast with the data that suggest that colour vision develops early in life, integration of contours (Kovács, 2000) or of the visual context (Káldy and Kovács, 2003) is not fully developed even at the age of 4-5 years. Káldy and Kovács (2003) examined the effect of visual context on size perception by means of the Ebbinghaus illusion (or Titchener circles , FIG.…”
Section: Development Of Form and Visual Context Perceptioncontrasting
confidence: 88%
See 1 more Smart Citation
“…However, studies with older children suggest that there is a protracted developmental trajectory for the ability to integrate local visual features spatially across the visual field [Hadad & Kimchi, 2006;Kovács, 2000;Kovács, Kozma, Feher, & Benedek, 1999]. In particular, several studies have reported that sensitivity to global structure in hierarchical visual stimuli, in which multiple levels of structure co-exist from the local elements to the global structure, is not fully mature even in late childhood and early adolescence [Burack, Enns, Iarocci, & Randolph, 2000;Dukette & Stiles, 1996;Enns, Burack, Iarocci, & Randolph, 2000;Mondloch, Geldart, Maurer, & de Schonen, 2003;Mottron et al, 1999;Porporino, Shore, Iarocci, & Burack, 2004].…”
Section: Development Of Perceptual Organization In Typical Individualsmentioning
confidence: 99%
“…There is also evidence that, though knowledge of contextual relationships in image structure begins to be acquired in the first few months of life, it continues to develop over several years in human vision. (Kovács 2000;Docherty et al in press). Figure 2.…”
Section: Dynamic Coordination In Cognition and Behaviormentioning
confidence: 99%